Employee Work Motivation Influenced By Internal Communication, Evaluation And Rewards - Pelupessy, Ig. Henri; Prabowo, Catur; Fahlefi, Diva Riza; Harminingtyas, Rudika (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Work motivation is the drive or enthusiasm that someone has to carry out tasks and responsibilities in the workplace. The purpose of this study was to determine and analyze the effect of internal communication, evaluation and reward on employee work motivation at PT. Grab Teknologi Indonesia in Semarang. The population in this study were 49 employees of PT. Grab Teknologi Indonesia in Semarang. The sampling technique used was saturated sampling and the sample was set to 49 respondents. The independent variables in this study were internal communication (X1), evaluation (X2) reward (X3) and the dependent variable was work motivation (Y). The data collection method in this study used a questionnaire with an analysis method using multiple linear regression, t-test and F-test and coefficient of determination. The results showed that the internal communication variable had a positive and significant effect on work motivation, then the evaluation variable had an insignificant effect on work motivation and the reward variable had a positive and significant effect on work motivation. The coefficient of determination (R Square) figure of 0.417, means that the internal communication, evaluation and reward variables have a role of 41.7% to explain the work motivation variable. Suggestions for improving internal communication in companies include developing more effective communication channels, such as digital platforms for feedback. This can strengthen relationships between employees and increase overall work motivation, then the evaluation process by emphasizing constructive feedback and personal development. Involve employees in setting evaluation goals and offer a variety of rewards, such as bonuses, awards, or self-development opportunities, so that employees can choose what ismost meaningful to them.